Environmental levels of avian antigen are relevant to the progression of chronic hypersensitivity pneumonitis during antigen avoidance. Issue 1 (22nd November 2017) - Sema, Manabu; Miyazaki, Yasunari; Tsutsui, Toshiharu; Tomita, Makoto; Eishi, Yoshinobu; Inase, Naohiko
Abstract: Background: In chronic hypersensitivity pneumonitis (chronic HP), antigen avoidance is critical for disease management; however, complete avoidance is difficult because of unrecognized exposure to antigens. Recently, we revealed that the amount of avian antigen (AAA) in household dust at the time of diagnosis predicted the progression of chronic bird‐related HP. The purpose of this study is to evaluate the relationship between the prognosis of chronic bird‐related HP and the AAA that remained in the environment during antigen avoidance. Methods: First, we measured the AAA in household dust of 28 consecutive patients (22 with chronic bird‐related HP and 6 with acute bird‐related HP) and 12 healthy volunteers. Second, we measured the AAA and collected questionnaires on the environmental conditions of the homes of 53 patients with various lung diseases, including bird‐related HP, to investigate the environmental parameters related to a higher AAA. Finally, we prospectively recruited 14 consecutive patients with chronic bird‐related HP, measured the AAA periodically, and collected clinical data. Results: The AAA was higher in patients with chronic bird‐related HP at the time of diagnosis compared to healthy volunteers and was highest in patients with acute bird‐related HP. Logistic regression analysis showed that birds frequenting a residence was the only significant factor for a higher AAA (odds ratio, 5.686; 95%CI, 1.263–25.59; P = 0.024). There was a correlation between the mean AAA and decline of vital capacity for 1 year ( r = −0.55; 95%CI −0.84 to −0.01; P = 0.043). Conclusion: Measurements of the AAA after diagnosis predict the progression of chronic bird‐related HP. Avian antigen can exist in the indoor environment regardless of antigen avoidance. The presence of avian antigen in the indoor environment can be attributed to wild birds found outdoors. Abstract : There was a correlation between the mean amount of avian antigen (AAA) and the decline of vital capacity for 1 year ( r = −0.55; 95%CI −0.84 to −0.01; P = 0.043). The annual decline in VC from baseline in the high‐level exposure group was higher than in the low‐level exposure group (≥0.74 µg/g of dust) (332 ± 89 ml vs. 53 ± 116 ml, P = 0.004). Measurements of AAA after diagnosis predict the progression of chronic bird‐related HP.